애니메이션 캐릭터의 젠더 정체성 - 성례아(Re-A Sung) (한국콘텐츠학회 논문지, 7(11), 2007)
The image calls forth the curiosity of the children. children experience the many thing through the image and it makes children to study naturally. Specially, the animation socializes children and it plays an important role in form of a self-identity. The gender-identity reappearance of the animation character is important. Gender-identity reappearance type of the animation character is able to classify with the reappearance type of visual information and the narrative. The narrative reappearance type does more clearly visual information reappearance type. Also classifying the gender-identity of animation character aspects into each type, they are; gender stereotype that character reflects the conservative and commercial ideology; gender non-stereotype that character doesn't reflect gender stereotype. But reappearance of the gender non-stereotype character as well, it is stopping in the exaggeration or the caricature of gender role of the character. Consequently the animation characters must be reappeared with the character which have the future oriented gender identity-as one human being that forms a value subjectively. The animation which reappears the future oriented gender-identity plants a proper self-perception and gender role in children and relaxes the traditional gender-identity which is already acquired. 영상은 어린이들의 호기심을 불러일으키고 많은 것을 접하게 하여 자연스러운 학습을 유도한다. 특히 애니메이션은 어린이들을 사회화시킴은 물론, 자아 정체성을 형성하는데 중요한 역할을 한다. 따라서 애니메이션 캐릭터의 젠더 정체성 재현은 중요하다. 애니메이션 캐릭터의 젠더 정체성의 재현 방식은 시각정보를 통한 재현방식과 내러티브를 통한 재현방식으로 나누어 볼 수 있으며, 내러티브를 통한 재현방식이 시각정보의 재현방식을 더욱 확고히 해줌을 알 수 있다. 또한 애니메이션 캐릭터의 젠더 정체성의 양상을 살펴보면, 보수적이고 상업적인 이데올로기를 투영하는 젠더 고정관념과 일치하는 캐릭터와 젠더 고정관념에서 탈피하고자하는 캐릭터로 구분되어 진다. 그러나 젠더 고정관념을 탈피하고자하는 캐릭터의 재현 역시 젠더 역할의 과장이나 희화를 통한 비판에 그치고 있다. 따라서 애니메이션 캐릭터들은, 여성이나 남성으로 구분되는 스테레오타입으로 재현되는 것이 아닌, 하나의 인간으로서의 가치를 주체적으로 형성해 가는, 미래지향적인 젠더 정체성을 가진 캐릭터들로 재현되어야 한다. 미래지향적인 젠더 정체성을 재현하는 애니메이션은 어린이들에게 올바른 자아 개념과 젠더 역할을 심어주며, 이미 획득된 전통적인 젠더 정체성을 완화시키는 역할을 수행한다.